C.01: CNSS K.G. McKenzie Memorial Prize in Clinical Research: Intrathecal morphine following lumbar fusion: a randomized, placebo-controlled trial. (17th June 2016) - Yavin, D; Dhaliwal, P; Whittaker, T; Hawboldt, GS; Jewett, GA; Casha, S; du Plessis, S
Abstract : Background: Despite the ease of intraoperative injection, intrathecal morphine (ITM) is rarely provided in lumbar spine surgery. We therefore sought to demonstrate the safety and efficacy of ITM following lumbar fusion.Methods: In this double-blind trial, 150 patients undergoing elective instrumented lumbar fusion were randomly assigned to receive a single injection of ITM (0.2 mg) or placebo (saline) prior to wound closure. Primary outcomes were postoperative pain on the visual-analog scale during the inital 24 hours after surgery and respiratory depression. Secondary outcomes included related adverse events, opioid requirements, and length of stay. Outcome curves were estimated in an intention-to-treat, repeated-measures analysis.Results: Age, disability, operative times, and pre-operative pain were similar in both groups. ITM was associated with less pain both at rest ( p< 0.002) and with movement ( p< 0.02) during the initial 24 hours following surgery. ITM did not increase the cumulative incidence of respiratory depression (hazard ratio 0.86, p= 0.66). While ITM reduced postoperative opioid requirements ( p <0.03), there was no significant difference in length of stay ( p =0.67). Adverse events did not significantly differ between groups. The early benefits of ITM on postoperative pain were no longer apparent after 48 hours.Conclusions: A single ITM injection safety reduces postoperative pain following lumbar fusion. (ClinicalTrials.gov NCT01053039)